Chiral transfer‐dictated self‐assembly of chiral block copolymers. Issue 5 (16th September 2021) - Li, Hao; Xiong, Bijin; Xu, Jiangping; Zhu, Jintao
Abstract: Chiral structures not only exist in nature widely, they also emerge in artificial systems, attracting myriad attentions due to their excellent mechanical, optical, electrical, and magnetic properties. Self‐assembly of chiral block copolymers (BCPs*), where at least one block consists of chiral centers, represents a facile strategy to form helical/spiral/network structures with a controlled chirality. Usually, morphological chirality of BCP* assemblies was closely associated with molecular and conformational chirality of the chiral block. Generally, chiral assemblies arose from molecular chirality of BCPs*, transferring up in the assembly process and dictated the chirality at a higher hierarchical level. In contrast, notwithstanding similar assemblies could be observed from achiral BCPs under certain conditions, both left‐ and right‐handed ones were usually observed simultaneously without a preference. Moreover, unique feature of BCPs* to access to controllable chiral assemblies affords an opportunity to prepare advanced functional materials. Herein, we dedicated a review on assembly of BCPs* into chiral assemblies in bulk/films, selective solvents, and confined spaces. The chiral transfer process in these assembly scenarios were discussed and highlighted as a key contributor to morphological chirality. Functionalities and representative applications of BCP* assemblies were also described, followed by present challenges and future prospects of BCP* self‐assembly. Abstract : The self‐assembly of chiral block copolymers (BCPs*) represents a facile access to controllable chiral structures. In this review, we presented the self‐assembly of BCPs* in bulk/films, selective solvents, and confined spaces. The chiral transfer process in these assembly scenarios were discussed and highlighted as a key contributor to the morphological chirality.